Clinical features, biochemistry and HLA-DRB1 status in children and adolescents with diabetes in Dhaka, Bangladesh. (December 2019) - Zabeen, Bedowra; Govender, Denira; Hassan, Zahid; Noble, Janelle Annette; Lane, Julie A.; Mack, Steven John; Atkinson, Mark Alvin; Azad, Kishwar; Wasserfall, Clive Henry; Ogle, Graham David
Abstract: Aims: Little information is published on diabetes in young people in Bangladesh. We aimed to investigate the demographic, clinical, and biochemical features, and HLA- DRB1 alleles in new cases of diabetes affecting Bangladeshi children and adolescents <22 years of age. Methods: The study was conducted at Bangladesh Institute of Research and Rehabilitation of Diabetes, Endocrine and Metabolic Disorders (BIRDEM) in Dhaka. One hundred subjects aged <22 years at diagnosis were enrolled. Demographic characteristics, clinical information, biochemical parameters (blood glucose, HbA1c, C-peptide, and autoantibodies against glutamic acid decarboxylase 65 (GADA) and islet antigen-2 (IA-2A) were measured. High-resolution DNA genotyping was performed for HLA-DRB1 . Results: Eighty-four subjects were clinically diagnosed as type 1 diabetes (T1D), seven as type 2 diabetes (T2D), and nine as fibrocalculous pancreatic disease (FCPD). Of the 84 with T1D, 37 (44%) were males and 47 (56%) females, with median age at diagnosis 13 years (y) (range 1.6–21.7) and peak age at onset 12–15 years. 85% of subjects were assessed within one month of diagnosis and all within eleven months. For subjects diagnosed with T1D, mean C-peptide was 0.46 ± 0.22 nmol/L (1.40 ± 0.59 ng/mL), with 9 (10.7%) IA-2A positive, 22 (26%) GADA positive, and 5 (6%) positive for both autoantibodies. Analysis of HLA- DRB1 genotypes revealed locus-level T1D association (p = 6.0E−05); DRB1*04:01 appeared predisposing (p < 3.0E−06), and DRB1*14:01 appeared protective (p = 1.7E−02). Conclusions: Atypical forms of T1D appear to be more common in young people in Bangladesh than in European populations. This will be helpful in guiding more specific assessment at onset and potentially, expanding treatment options.